O busto do Rei D. Fernando II, do Palácio Nacional da Pena : conservação e restauro com a aplicação da técnica de limpeza a laser - Chaves, Débora Neves (2022)
The realization of this theoretical and practical work consists in the intervention of restoration in the plaster bust of D. Fernando II, the King Consort of Portugal. This work belongs to the Pena National Palace, in Sintra, and presented some pathologies that impaired the preservation of the work, namely some dark spots that were supposed to be small biological colonization caused by humidity. The final goal, after the end of this project, is that the work be exposed to the public, in the Pena National Palace. Thus, in view of this pathology visible to the naked eye, a cleaning methodology by selective ablation was carried out – Laser Cleaning – in collaboration with the conservator-restorer Adélia Gomes, from the company Statua, Atelier de Escultura, Conservação e Restauro Lda., to remove these stains that disturbed the reading of the work. The use of this technique as an alternative plan was considered after some previous cleaning tests with little efficacy in the removal of this pathology. And although this method is widely used in the scientific field of Conservation and Restoration, it does not have much prominence in plaster sculpture in Portugal. In addition to the intervention in the bust, the target of study of this project, there is another issue of interest to mention: this work may have been the original from which the mold was removed for the creation of replicas. During the execution of the present work, a total of seven known replicas (not counting the case of study) were identified, which are in the possession of several Portuguese institutions with connection with King Fernando II. through a methodology with little documentary investment in Conservation and Restoration of Plaster Sculpture, in Portugal. But it also serves as an elucidative document of issues related to plaster art, molds, replica and copying.